1993
DOI: 10.1080/03946975.1993.10539209
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biology and aquaculture potential of feral catfishHeterobranchus bidorsalis(Geoffroy St. Hilaire 1809) (Clariidae)

Abstract: Haematological profile of Heterobranchus bidorsalis (Geoffroy St. Hilaire 1809) was determined. Haematocrit values, haemoglobin concentrations, erythrocyte and leucocyte counts, mean cell haemoglobin concentration, sodium and potassium ions concentrations were 24.75±1.23%, 5.43±0.25 g/100 ml, 1.99±0.52 10"/mm 3 and 7.25±0.60 10 4 /mm 3 , 22.11±0.77%, 802.52±36.97 and 83.54±5.05 mgfl, respectively.H. bidorsalis fingerlings were subjected to a range of salinities, 0, 3, 6, 9, 12 and 15 ppt. The optimum salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
4
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 30 publications
6
46
4
2
Order By: Relevance
“…The blood parameters observed were similar to those reported for H. bidorsalis [25]. The direct proportion between the value of PCV, ESR and Hb of C. gariepinus showed that the increase in PCV increased the Hb concentration in the blood of the fish.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The blood parameters observed were similar to those reported for H. bidorsalis [25]. The direct proportion between the value of PCV, ESR and Hb of C. gariepinus showed that the increase in PCV increased the Hb concentration in the blood of the fish.…”
Section: Discussionsupporting
confidence: 73%
“…Erythrocyte Sedimentation Rate decreased with increasing D. elliptica concentrations and has been used to ascertain the response of fish blood to stress, pollution, diseases, starvation and nutritional deficiency [24]. Mean corpuscular haemoglobin concentration (MCHC) values reported for Oreochromis niloticus, Heterobranchus bidorsalis and other African fishes were comparable to those of C. gariepinus [25].…”
Section: Discussionmentioning
confidence: 99%
“…No information is available on the quantitative and qualitative assays of digestive enzyme in the gut of H. niloticus, in contrast to other African freshwater fishes whose digestive enzymes assays have been established (OLATUNDE & OGUNBIYI 1976, AKINTUNDE 1985, UYS & HECHT 1987, OLATUNDE et al 1988, FAGBENRO 1990, FAGBENRO et al 1993. In this paper, the occurrence, distribution and relative activities of glycosidases, proteases and lipases in the different gut regions (oesophagus, stomach, pyloric caeca, ileum, rectum) of H. niloticus are described for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…This African catfish is widely distributed throughout Africa, inhabiting tropical swamps, lakes and rivers, some of which are subjected to seasonal drying [1]. However, farmers are constraint with massive fry and fingerling mortalities, especially in culture system due to the invasion of parasites [7] [8].…”
Section: Introductionmentioning
confidence: 99%